Improving Students' Reading Comprehension Skill By Using CIRC - Audy Alya Batara; Jusriati; Nasriandi (Universitas Islam Negeri Palopo, 2025)
The Cooperative Integrated Reading and Composition (CIRC) method is a cooperative learning method used to develop language skills such as reading and writing in the classroom at the high school level. This study used a Quasi-experimental design because it aims to investigate whether the teaching technique has a significant impact on students' reading comprehension. In this study, eleventh grade students of SMA 6 Palopo in the academic year 2023/2024 were selected as the object of research. Students in the experimental group after the treatment were in the good and quite good classification, while the control group was in the quite bad classification. The mean scores of the experimental group and control group in the pre-test and post-test were 74.11 and 64.11, respectively, with standard deviations of 16.885 and 13.833. After treatment with the CIRC method, the mean scores of students in both groups were higher than those in the non-CIRC treatment group. The results showed that the treatment in the control group and the experimental group showed significant improvement in students' reading comprehension achievement. In conclusion, the application of Cooperative Integrative Reading Composition has shown promising results in improving students' English learning, especially in reading narrative texts.